THEORY OF LAW AND COMPUTER CRIMES TEORIA DO DIREITO E CRIMES INFORMÁTICOS - Mangiameli (Universidade de Roma – Tor Vergata), Agata C. Amato (Duc In Altum - Cadernos de Direito, 2017)
This paper aims investigate the general theory and the elements of the computer crimes as well it social engineering, because as technology advances, more and more people use it according to their needs.